A method for preparing a balloon dilatation catheter material for prostate hyperplasia
By adding chitosan and gelatin composite microcapsules to the balloon dilated catheter material, the internal filling of polyurethane prepolymers and benzophenone containing carbon-carbon double bonds can achieve self-healing of the material, solving the limitations of existing materials in terms of biocompatibility, mechanical properties and long-term use stability, and improving the reliability and stability of the catheter.
Patent Information
- Application Number
- CN202411990473.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing balloon dilated catheter materials have limitations in biocompatibility, mechanical properties and long-term use stability, especially in complex clinical settings that are prone to damage, resulting in increased patient infection risk.
By adding microcapsules to the material, the wall material of the microcapsules uses a composite of chitosan and gelatin. The internally filled repairing agent is a mixture of polyurethane prepolymers and benzophenone containing carbon-carbon double bonds. It uses photo-induced and enzyme-catalyzed reactions to form a crosslinking network structure to achieve self-healing of the material.
It improves the biocompatibility and mechanical properties of the material, has self-healing function, and can restore its original mechanical properties and functions when a material is damaged in microscopic, ensuring the reliability and stability of the catheter in use.
Smart Images

Figure CN119770748A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical materials, and in particular to a method for preparing a balloon dilatation catheter material for prostate hyperplasia. Background Art
[0002] In the treatment of prostatic hyperplasia, balloon dilatation catheters play an important role as a key treatment device. Their main function is to relieve urethral stenosis by mechanically dilating prostate tissue, thereby improving the patient's urination function. Therefore, the performance of balloon dilatation catheters has a direct impact on the treatment effect. At present, although the widely used balloon dilatation catheter materials can meet clinical needs to a certain extent, they still have some limitations in terms of biocompatibility, mechanical properties and stability in long-term use.
[0003] Patent publication number CN108478883A discloses a method for preparing a stretch-resistant medical catheter material and its application. The medical catheter material prepared by the method has good tensile properties and high biological safety.
[0004] The patent with announcement number CN113480799B discloses a medical EVA catheter material with a frosted surface effect, a preparation method and an application. The medical EVA catheter material produced by the invention has good softness and resilience, does not add plasticizers, is safe and non-toxic, and meets the requirements of catheters for transporting aqueous solutions, fat emulsions, proteins and other infusion drugs. Its biocompatibility and applicable drug range are better than similar products of PVC and TPE materials, ensuring the health and safety of patients.
[0005] Therefore, from the existing technology, the improvement direction for medical catheter materials is mostly to improve the biocompatibility and tensile strength of the materials. However, in some complex clinical treatment environments, especially as a balloon dilatation catheter for prostate hyperplasia, the balloon part of the catheter may be affected by external forces or damaged during use. If the catheter material cannot quickly recover or repair its structure after damage, it may increase the risk of infection for patients.
[0006] Therefore, the present invention provides a new type of balloon dilatation catheter material, which not only improves its biocompatibility and mechanical properties, but also has a self-repair function. When the material is micro-damaged, it can restore its original mechanical properties and functions, thereby ensuring the reliability and stability of the catheter during use. Summary of the invention
[0007] The main purpose of the present invention is to provide a method for preparing a balloon dilatation catheter material for prostate hyperplasia, which can effectively solve the problems in the background technology.
[0008] To achieve the above purpose, the technical scheme adopted by the present invention is as follows: by adding microcapsules to the material, the wall material of the microcapsules adopts a composite of chitosan and gelatin, and a stable capsule wall structure is formed through electrostatic interaction and hydrogen bonding. The repair agent filled inside is a mixture of a polyurethane prepolymer containing carbon-carbon double bonds and benzophenone. Benzophenone is used as a photoinitiator. When microrupture occurs in vitro, benzophenone generates free radicals under ultraviolet light irradiation. The free radicals can trigger the polymerization reaction of the double bonds in the polyurethane prepolymer, thereby forming a cross-linked network structure or a high molecular polymer to perform self-repair of the material; and when microrupture occurs in the material in vivo, the polyurethane prepolymer containing carbon-carbon double bonds reacts with the free amino groups (–NH 2 ) groups react to form carbamate bonds. Through this reaction, hybrid polyurethane network materials can be prepared to form a cross-linked structure and complete self-repair.
[0009] A method for preparing a balloon dilatation catheter material for prostate hyperplasia comprises the following specific steps:
[0010] S1: Preparation of microcapsules;
[0011] S2: Prepare the raw materials of each component according to the following weight parts: 50-100 parts of waterborne polyurethane, 50-100 parts of polyvinyl alcohol, 20-50 parts of compatibilizer, 0.3-0.6 parts of crosslinking agent, 10-30 parts of carbon nanotubes, 30-60 parts of microcapsules, and 40-60 parts of polycaprolactone;
[0012] S3: adding the weighed polycaprolactone into the reaction kettle, heating it to 160-180°C to melt it, and then stirring it at a speed of 200-300 rpm for 8-12 minutes to obtain a uniform polycaprolactone melt;
[0013] S4: Cool the polycaprolactone melt to 100-120°C, add waterborne polyurethane, polyvinyl alcohol and compatibilizer, and stir at a speed of 500-700 rpm for 15-25 minutes to fully mix the components;
[0014] S5: Slowly add the crosslinking agent according to the proportion, and continue stirring for 10-15 minutes to ensure that the crosslinking reaction proceeds evenly;
[0015] S6: Cool down to 60-80°C, add carbon nanotubes and prepared microcapsules, and stir at a high speed of 800-1000 rpm for 20-30 minutes to make the carbon nanotubes evenly dispersed in the material system and the microcapsules completely and evenly embedded in the material;
[0016] S7: putting the above mixed materials into a twin-screw extruder, setting the extrusion temperature to 170-200°C and the screw speed to 20-40rpm, and obtaining a balloon dilatation catheter material for prostate hyperplasia through extrusion, cooling, pulling and cutting.
[0017] Preferably, in S2, the compatibilizer is specifically a maleic anhydride grafted polymer, and the cross-linking agent is specifically glutaraldehyde.
[0018] Preferably, in S5, the cross-linking agent is slowly added dropwise at a speed of 0.5-1 ml / min.
[0019] Preferably, the waterborne polyurethane is a waterborne polyurethane containing free amino groups.
[0020] Preferably, the microcapsule is made of a wall material and an inner liquid, the wall material is made of chitosan and gelatin, and the mass ratio of chitosan to gelatin is 3:2, the inner liquid includes a polyurethane prepolymer containing carbon-carbon double bonds and benzophenone and glutamine transaminase, and the mass ratio of the polyurethane prepolymer to benzophenone is 10:1.
[0021] More preferably, the specific preparation steps of the microcapsules are as follows:
[0022] S11: dissolving chitosan in a dilute acetic acid solution to prepare a chitosan solution with a concentration of 2% to 3% (w / v), dissolving gelatin in deionized water to prepare a gelatin solution with a concentration of 3% to 4% (w / v), and mixing the two solutions at 40-50° C. according to a proportion to obtain a wall material solution;
[0023] S12: a polyurethane prepolymer containing a carbon-carbon double bond and benzophenone are mixed in proportion, stirred evenly, and then a proper amount of emulsifier is added to form a uniform emulsion under high-speed stirring (800-1000 rpm), and then glutamine aminotransferase is added as a catalyst contained in the microcapsules, and the added mass is 1% of the polyurethane prepolymer containing a carbon-carbon double bond;
[0024] S13: slowly dropwise adding the above emulsion into the wall material solution, while stirring at a speed of 300-500 rpm, so that the emulsion is dispersed into tiny droplets in the wall material solution;
[0025] S14: then adding glutaraldehyde to crosslink and solidify the wall material using glutaraldehyde, wherein the amount of glutaraldehyde added is 0.5% to 1% of the mass of the wall material solution, and the crosslinking reaction is carried out at room temperature for 2 to 3 hours, during which the mixture is continuously stirred at a rotation speed of 500 to 600 rpm;
[0026] S15: After the cross-linking is completed, the microcapsules are collected by centrifugal separation, and washed with deionized water for 3-4 times to remove unreacted substances and impurities to obtain pure microcapsules.
[0027] Preferably, in S12, the emulsifier is a 10% to 20% (w / v) aqueous solution of behenyl alcohol polyoxyethylene ether-80.
[0028] Preferably, the specific mass of the behenyl alcohol polyoxyethylene ether-80 aqueous solution added is 1% to 3% of the total mass of the polyurethane prepolymer containing carbon-carbon double bonds and benzophenone.
[0029] Preferably, in S13, the specific speed of slowly dropping the emulsion into the wall material solution is 1-2 drops / s.
[0030] Preferably, in S15, the time for centrifuging the microcapsules is 10-15 minutes, and the speed of centrifugation is 3000-5000 rpm.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention adopts water-based polyurethane, polyvinyl alcohol, and polycaprolactone. Polycaprolactone is a material with high biocompatibility and degradability. It is used as a substrate to provide a good biocompatibility foundation and structural support for the entire material system, and can be gradually degraded in the body to reduce the risk of long-term residual. Polyvinyl alcohol further enhances the hydrophilicity and biocompatibility of the material, helps to reduce thrombosis and inflammatory response, improves the adaptability of the material in the body, and gives the material good flexibility and elasticity, so that it can adapt to shape changes during balloon expansion and reduce damage to prostate tissue. Carbon nanotubes significantly enhance the mechanical properties of the material, improve the strength and fatigue resistance during balloon expansion, and ensure the reliability of the catheter during use.
[0033] 2. The present invention adds microcapsules as self-repairing materials. The wall material of the microcapsules is a composite of chitosan and gelatin. The repair agent filled inside the microcapsules is a mixture of a polyurethane prepolymer containing carbon-carbon double bonds and benzophenone. When microcracks occur in vitro, benzophenone generates free radicals under the irradiation of ultraviolet light in the external environment. The free radicals can trigger the polymerization reaction of the double bonds in the polyurethane prepolymer, thereby forming a cross-linked network structure or a high molecular polymer to perform self-repair of the material. When microcracks occur in the material in vivo, the polyurethane prepolymer containing carbon-carbon double bonds reacts with the free amino groups in the water-based polyurethane to generate carbamate bonds, forming a cross-linked structure, and completing the self-repair of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the overall structure of the present invention;
[0035] Figure 2 This is an electron microscope image of the microcapsules prepared in the present invention. DETAILED DESCRIPTION
[0036] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0037] The invention discloses a method for preparing a balloon dilatation catheter material for prostate hyperplasia. The material is specifically used as an outer layer material of the balloon dilatation catheter.
[0038] The present invention combines waterborne polyurethane (WPU), polyvinyl alcohol (PVA), polycaprolactone (PCL) and maleic anhydride grafted polymer (MAH-grafted polymer) as compatibilizers, and uses glutaraldehyde as a basic formula of a cross-linking agent, and adds microcapsules as a self-healing material, so that the present invention has good self-healing performance;
[0039] Among them, polycaprolactone is a material with high biocompatibility and degradability. As a substrate, it provides a good biocompatibility foundation and structural support for the entire material system. It can be gradually degraded in the body to reduce the risk of long-term residues. Polyvinyl alcohol further enhances the hydrophilicity and biocompatibility of the material, helps to reduce thrombosis and inflammatory response, improves the adaptability of the material in the body, and gives the material good flexibility and elasticity, so that it can adapt to shape changes during balloon expansion and reduce damage to prostate tissue; carbon nanotubes significantly enhance the mechanical properties of the material, improve the strength and fatigue resistance during balloon expansion, and ensure the reliability of the catheter during use.
[0040] The waterborne polyurethane in the present invention is a waterborne polyurethane containing free amino groups, and the waterborne polyurethane containing free amino groups can be specifically prepared by reacting hexamethylenediamine with polyether diol to obtain a polyether prepolymer having free amino groups.
[0041] The reaction equation is as follows:
[0042] HO-R-OH+H 2 N-CH 2 CH 2 NH 2 →HO-R-NH-CH 2 CH 2 NH 2 +H 2 O;
[0043] Among them, HO-R-OH represents polyether diol, H 2 N-CH 2 CH 2 NH 2 stands for ethylenediamine;
[0044] In the prepolymer generated by the reaction, ethylenediamine reacts with the hydroxyl group of the polyether diol, resulting in the formation of a structure with a free amino group at the end of the polyether chain. During the reaction, the amount of isocyanate is appropriately reduced to ensure that the free amino group does not completely react with the isocyanate. This can avoid the reaction of all amino groups to form carbamate bonds, leaving some free amino groups, and obtaining a water-based polyurethane with free amino groups.
[0045] In addition, the present invention adds specially prepared microcapsules to the material, and the microcapsules prepared by the preparation method disclosed in the present invention, such as Figure 2 As shown, the particle size is maintained at 1-10 μm. The wall material of the microcapsule is a composite of chitosan and gelatin. A stable capsule wall structure is formed through electrostatic interaction and hydrogen bonding. The capsule has a certain degree of brittleness and can release the contents faster when ruptured. The repair agent filled inside is a mixture of a polyurethane prepolymer containing carbon-carbon double bonds and benzophenone. Benzophenone is used as a photoinitiator. When microrupture occurs in vitro, benzophenone generates free radicals under the irradiation of ultraviolet light in the external environment. The free radicals can trigger the polymerization reaction of the double bonds in the polyurethane prepolymer, thereby forming a cross-linked network structure or a high molecular polymer to perform self-repair of the material.
[0046] When micro-ruptures occur in the material in vivo, the glutamine aminotransferase in the microcapsule can activate the free amino groups in the water-based polyurethane, enhancing its nucleophilicity. By forming an enzyme-substrate complex with the amino group, it changes the chemical environment around the amino group, making it easier to attack the carbon-carbon double bond. This activation involves hydrogen bonds and electrostatic interactions between the active sites on the enzyme molecules and the amino groups, thereby generating urethane bonds. Through this reaction, hybrid polyurethane network materials can be prepared to form cross-linked structures and complete self-repair.
[0047] The optimum temperature for glutamine transaminase is between 30-50°C. Within this temperature range, the enzyme is more active and the molecular movement is faster, which increases the frequency of collisions between carbon-carbon double bonds and amino groups. For example, at 37°C (close to human body temperature), the active structure of the enzyme molecule can maintain good flexibility and activity, which is conducive to the rapid reaction.
[0048] The polyurethane prepolymer containing carbon-carbon double bonds is prepared by introducing unsaturated monomers (such as unsaturated diols or unsaturated isocyanates) during the synthesis process. During the synthesis process, the monomer containing unsaturated bonds reacts with conventional polyurethane constituent monomers to generate polyurethane prepolymer containing carbon-carbon double bonds. This is common chemical knowledge and will not be described in detail. The polyurethane prepolymer introduced with C=C double bonds has strong crosslinking and curing capabilities and can react with free amino groups (–NH 2 ) groups react to cross-link and cure.
[0049] In addition, in the present invention, maleic anhydride grafted polymer is used as a compatibilizer to improve the compatibility between polyurethane and other aqueous materials and enhance the stability of the material. Glutaraldehyde is used as a cross-linking agent to induce intermolecular cross-linking and enhance the mechanical strength, water resistance and biodegradability of the substrate.
[0050] The following is a detailed description of the method for preparing the balloon dilatation catheter material for prostate hyperplasia disclosed in the present invention in conjunction with specific embodiments and comparative examples:
[0051] Embodiment 1
[0052] This embodiment prepares the method for preparing the balloon dilatation catheter material for prostate hyperplasia disclosed in the present invention according to the following steps:
[0053] S1. Prepare materials: prepare microcapsules. The specific method is as follows;
[0054] S11, dissolving chitosan in a dilute acetic acid solution to prepare a chitosan solution with a concentration of 2.5% (w / v), dissolving gelatin in deionized water to prepare a gelatin solution with a concentration of 3.5% (w / v), and mixing the two solutions at 45° C. in proportion to obtain a wall material solution;
[0055] S12. The polyurethane prepolymer containing carbon-carbon double bonds and benzophenone are mixed in proportion, stirred evenly, and then an appropriate amount of emulsifier is added to form a uniform emulsion under high-speed stirring (950 rpm), and then glutamine aminotransferase is added as a catalyst contained in the microcapsules, and the added mass is 1% of the polyurethane prepolymer containing carbon-carbon double bonds; in this embodiment, the emulsifier is specifically a 15% (w / v) aqueous solution of polyoxyethylene behenyl alcohol ether-80, and the specific mass of the 15% (w / v) aqueous solution of polyoxyethylene behenyl alcohol ether-80 added is 2% of the total mass of the polyurethane prepolymer containing carbon-carbon double bonds and benzophenone.
[0056] S13, then adding the above emulsion to the wall material solution at a rate of 1 drop / s, while stirring at a speed of 350 rpm, so that the emulsion is dispersed into tiny droplets in the wall material solution;
[0057] S14, then adding glutaraldehyde as a cross-linking agent, using glutaraldehyde to cross-link and solidify the wall material, the amount of glutaraldehyde added is 0.5% of the mass of the wall material solution, and the cross-linking reaction is carried out at room temperature for 2 hours, during which the stirring is continuously carried out at a rotation speed of 550 rpm;
[0058] S15, after the cross-linking is completed, the microcapsules are collected by centrifugation at a rotation speed of 3450 rpm for 12 minutes, and washed with deionized water for 4 times to remove unreacted substances and impurities to obtain pure microcapsules;
[0059] S2. Prepare the raw materials of each component according to the following weight parts: 75 parts of aqueous polyurethane containing free amino groups, 75 parts of polyvinyl alcohol, 30 parts of maleic anhydride grafted polymer, 0.4 parts of glutaraldehyde, 18 parts of carbon nanotubes, 45 parts of microcapsules, and 45 parts of polycaprolactone;
[0060] S3, adding the weighed polycaprolactone into the reaction kettle, heating it to 165° C. to melt it, and then stirring it at a speed of 250 rpm for 9 minutes to obtain a uniform polycaprolactone melt;
[0061] S4: Cooling the polycaprolactone melt to 100°C, adding waterborne polyurethane, polyvinyl alcohol and maleic anhydride grafted polymer, stirring at 600 rpm for 20 minutes to fully mix the components;
[0062] S5: Add glutaraldehyde dropwise at a rate of 1 ml / min according to the proportion, and continue stirring for 15 min to ensure that the cross-linking reaction proceeds evenly;
[0063] S6: Cooling to 65°C, adding carbon nanotubes and prepared microcapsules, stirring at a high speed of 800-1000 rpm for 25 minutes, so that the carbon nanotubes are evenly dispersed in the material system, and the microcapsules are completely and evenly embedded in the material;
[0064] S7: The mixed material is put into a twin-screw extruder, the extrusion temperature is set to 180° C., the screw speed is 35 rpm, and after extrusion, cooling, pulling and cutting, a balloon dilatation catheter material for prostate hyperplasia is obtained.
[0065] Example 2
[0066] This embodiment prepares the method for preparing the balloon dilatation catheter material for prostate hyperplasia disclosed in the present invention according to the following steps:
[0067] S1. Prepare materials: prepare microcapsules. The specific method is as follows;
[0068] S11, then dissolving chitosan in a dilute acetic acid solution to prepare a chitosan solution with a concentration of 2% (w / v), dissolving gelatin in deionized water to prepare a gelatin solution with a concentration of 3% (w / v), and mixing the two solutions at 40° C. according to a proportion to obtain a wall material solution;
[0069] S12. A polyurethane prepolymer containing a carbon-carbon double bond and benzophenone are mixed in proportion, stirred evenly, and then an appropriate amount of an emulsifier is added to form a uniform emulsion under high-speed stirring (800 rpm), and then glutamine aminotransferase is added as a catalyst contained in the microcapsules, and the added mass is 1% of the polyurethane prepolymer containing a carbon-carbon double bond; wherein the emulsifier is specifically a 10% (w / v) aqueous solution of polyoxyethylene behenyl alcohol ether-80, and the specific mass of the 10% (w / v) aqueous solution of polyoxyethylene behenyl alcohol ether-80 is 1% of the total mass of the polyurethane prepolymer containing a carbon-carbon double bond and benzophenone.
[0070] S13, then adding the above emulsion to the wall material solution at a rate of 1 drop / s, while stirring at a speed of 300 rpm, so that the emulsion is dispersed into tiny droplets in the wall material solution;
[0071] S14, then adding glutaraldehyde as a cross-linking agent, using glutaraldehyde to cross-link and solidify the wall material, the amount of glutaraldehyde added is 0.5% of the mass of the wall material solution, and the cross-linking reaction is carried out at room temperature for 2 hours, during which the mixture is continuously stirred at a rotation speed of 500 rpm;
[0072] S15. After the cross-linking is completed, the microcapsules are collected by centrifugal separation at a rotation speed of 3000 rpm for 10 minutes, and washed with deionized water for 4 times to remove unreacted substances and impurities to obtain pure microcapsules.
[0073] S2. Prepare the raw materials of each component according to the following weight parts: 50 parts of aqueous polyurethane containing free amino groups, 50 parts of polyvinyl alcohol, 20 parts of maleic anhydride grafted polymer, 0.3 parts of glutaraldehyde, 10 parts of carbon nanotubes, 30 parts of microcapsules, and 40 parts of polycaprolactone;
[0074] S3, adding the weighed polycaprolactone into the reaction kettle, heating it to 160° C. to melt it, and then stirring it at a speed of 200 rpm for 8 minutes to obtain a uniform polycaprolactone melt;
[0075] S4: Cool the polycaprolactone melt to 100°C, add waterborne polyurethane, polyvinyl alcohol and maleic anhydride grafted polymer, and stir at 500 rpm for 15 minutes to fully mix the components;
[0076] S5: Add glutaraldehyde dropwise at a rate of 0.5 ml / min according to the proportion, and continue stirring for 10-15 minutes to ensure that the cross-linking reaction proceeds evenly;
[0077] S6: Cooling to 60°C, adding carbon nanotubes and prepared microcapsules, and stirring at a high speed of 800 rpm for 20 minutes to make the carbon nanotubes evenly dispersed in the material system and the microcapsules completely and evenly embedded in the material;
[0078] S7: The mixed material is put into a twin-screw extruder, the extrusion temperature is set to 170° C., the screw speed is set to 20 rpm, and after extrusion, cooling, pulling and cutting, a balloon dilatation catheter material for prostate hyperplasia is obtained.
[0079] Example 3
[0080] This embodiment prepares the method for preparing the balloon dilatation catheter material for prostate hyperplasia disclosed in the present invention according to the following steps:
[0081] S1. Prepare materials: prepare microcapsules. The specific method is as follows;
[0082] S11, then dissolving chitosan in a dilute acetic acid solution to prepare a chitosan solution with a concentration of 3% (w / v), dissolving gelatin in deionized water to prepare a gelatin solution with a concentration of 4% (w / v), and mixing the two solutions at 50° C. according to a proportion to obtain a wall material solution;
[0083] S12. A polyurethane prepolymer containing a carbon-carbon double bond and benzophenone are mixed in proportion, stirred evenly, and then an appropriate amount of an emulsifier is added to form a uniform emulsion under high-speed stirring (1000 rpm), and then glutamine aminotransferase is added as a microcapsule-containing catalyst, and the added mass is 1% of the polyurethane prepolymer containing a carbon-carbon double bond; wherein the emulsifier is specifically a 20% (w / v) aqueous solution of polyoxyethylene behenyl alcohol ether-80, and the specific mass of the 20% (w / v) aqueous solution of polyoxyethylene behenyl alcohol ether-80 is 3% of the total mass of the polyurethane prepolymer containing a carbon-carbon double bond and benzophenone.
[0084] S13, then adding the above emulsion to the wall material solution at a speed of 2 drops / s, while stirring at a speed of 500 rpm, so that the emulsion is dispersed into tiny droplets in the wall material solution;
[0085] S14, then adding glutaraldehyde as a cross-linking agent, using glutaraldehyde to cross-link and solidify the wall material, the amount of glutaraldehyde added is 1% of the mass of the wall material solution, and the cross-linking reaction is carried out at room temperature for 3 hours, during which the mixture is continuously stirred at a rotation speed of 600 rpm;
[0086] S15. After the cross-linking is completed, the microcapsules are collected by centrifugal separation at a rotation speed of 5000 rpm for 15 minutes, and washed with deionized water for 4 times to remove unreacted substances and impurities to obtain pure microcapsules.
[0087] S2. Prepare the raw materials of each component according to the following weight parts: 100 parts of aqueous polyurethane containing free amino groups, 100 parts of polyvinyl alcohol, 50 parts of maleic anhydride grafted polymer, 0.6 parts of glutaraldehyde, 30 parts of carbon nanotubes, 60 parts of microcapsules, and 60 parts of polycaprolactone;
[0088] S3, adding the weighed polycaprolactone into the reaction kettle, heating it to 180° C. to melt it, and then stirring it at a speed of 300 rpm for 12 minutes to obtain a uniform polycaprolactone melt;
[0089] S4: Cool the polycaprolactone melt to 120°C, add waterborne polyurethane, polyvinyl alcohol and maleic anhydride grafted polymer, and stir at 700 rpm for 25 min to fully mix the components;
[0090] S5: Add glutaraldehyde dropwise at a rate of 1 ml / min according to the proportion, and continue stirring for 15 min to ensure that the cross-linking reaction proceeds evenly;
[0091] S6: Cooling to 80°C, adding carbon nanotubes and prepared microcapsules, stirring at a high speed of 1000 rpm for 30 minutes, so that the carbon nanotubes are evenly dispersed in the material system, and the microcapsules are completely and evenly embedded in the material;
[0092] S7: The mixed material is put into a twin-screw extruder, the extrusion temperature is set to 200° C., the screw speed is 40 rpm, and after extrusion, cooling, pulling and cutting, a balloon dilatation catheter material for prostate hyperplasia is obtained.
[0093] Comparative Example 1
[0094] The difference between this comparative example and Example 1 is that no microcapsules and carbon nanotubes are added in this example.
[0095] Comparative Example 2
[0096] The only difference between this comparative example and Example 1 is that in this example, the waterborne polyurethane containing free amino groups is replaced by a waterborne polyurethane without free amino groups.
[0097] Comparative Example 3
[0098] The only difference between this comparative example and Example 1 is that in this example, the polyurethane prepolymer containing carbon-carbon double bonds used in preparing microcapsules is replaced by a polyurethane prepolymer not containing carbon-carbon double bonds.
[0099] The samples prepared in Examples 1-3 and Comparative Examples 1-3 were tested for their performance, specifically:
[0100] 1. Expansion fatigue test
[0101] The following test standards are formulated with reference to the industry standards and research methods of fatigue testing of related medical devices. The balloon dilatation catheter material is made into a balloon shape and installed on a specially designed fatigue testing device. The pressure is repeatedly filled and released at a frequency of 0.5 Hz in the pressure range of 0.5-3 MPa until the balloon ruptures or the elastic modulus drops below 70% of the initial value. The number of cycles is recorded as the number of expansion fatigue. The test environment temperature is maintained at (37 ± 1) ° C to simulate the human body environment. The results are shown in Table 1.
[0102] 2. Self-repair rate test
[0103] First, the initial tensile strength of the material was determined according to the tensile strength test standard. Then, a scratch with a depth of 0.5 mm and a length of 5 mm was made on the surface of the sample to simulate material damage. The damaged sample was placed in an environment with a temperature of (37±1)℃ and a relative humidity of 90% for 48 hours to allow the repair agent in the microcapsule to work and repair. After the repair was completed, the sample was tested again according to the tensile strength test standard, and the ratio of the tensile strength after repair to the initial tensile strength was calculated and multiplied by 100% to obtain the self-repair efficiency. The results are shown in Table 1.
[0104] Table 1, expansion fatigue times and self-repair rate performance test results of samples prepared in Examples 1-3 and Comparative Examples 1-3:
[0105]
[0106] 3. Dissolution content test
[0107] The content of dissolved matter was tested according to GB / T14233.1-2008 "Test methods for medical infusion, transfusion and injection equipment Part 1: Chemical analysis methods". The balloon dilatation catheter material was immersed in simulated human plasma (PBS buffer with pH 7.4) and placed at (37±1)℃ for 1 month. The content of organic matter that may be dissolved in the immersion solution was then determined by high performance liquid chromatography (HPLC), and the content of metal ions was determined by atomic absorption spectrometry (AAS). The results are shown in Table 2.
[0108] Table 2, test results of sample dissolution content prepared in Examples 1-3 and Comparative Examples 1-3:
[0109]
[0110] It can be seen from Table 1 that the samples prepared in Examples 1-3 of the present invention all have good expansion fatigue resistance and good self-repair rate. In particular, the samples prepared by the specific formula of each component in Example 1 have the highest number of anti-fatigue times and a self-repair rate of 95%. It can be seen that the specific formula of each component in Example 1 is the optimal embodiment of the present invention. At the same time, it can be seen from the test results of Comparative Example 1 that when the microcapsules disclosed in the present invention are not added, the prepared samples do not have self-repair ability. At the same time, when carbon nanotubes are not added, the expansion fatigue times are also significantly reduced. It can be seen from the test results of Comparative Examples 2 and 3 that when the polyurethane prepolymer containing carbon-carbon double bonds used in the present invention is used as the content of the microcapsule, it works together with the water-based polyurethane containing free amino groups, and its expansion fatigue times and self-repair rate are significantly improved.
[0111] It can be seen from Table 2 that the samples prepared in Examples 1-3 of the present invention all have relatively good chemical stability, and the lower content of dissolved matter generally indicates that the material is not prone to degradation or chemical reaction under physiological conditions, and can maintain the stability of its own structure and performance. This is very important for the long-term use of balloon dilatation catheters in vivo. If the material stability is poor, it may lead to a decrease in the mechanical properties of the catheter, structural damage, affecting the treatment effect and increasing the risk of surgery.
[0112] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a balloon dilatation catheter material for prostate hyperplasia, characterized in that: The specific steps include: S1: Preparation of microcapsules; S2: Prepare the raw materials of each component according to the following weight parts: 50-100 parts of waterborne polyurethane, 50-100 parts of polyvinyl alcohol, 20-50 parts of compatibilizer, 0.3-0.6 parts of crosslinking agent, 10-30 parts of carbon nanotubes, 30-60 parts of microcapsules, and 40-60 parts of polycaprolactone; S3: adding the weighed polycaprolactone into the reaction kettle, heating it to 160-180°C to melt it, and then stirring it at a speed of 200-300 rpm for 8-12 minutes to obtain a uniform polycaprolactone melt; S4: Cool the polycaprolactone melt to 100-120°C, add waterborne polyurethane, polyvinyl alcohol and compatibilizer, and stir at a speed of 500-700 rpm for 15-25 minutes to fully mix the components; S5: Slowly add the crosslinking agent according to the proportion, and continue stirring for 10-15 minutes to ensure that the crosslinking reaction proceeds evenly; S6: Cool down to 60-80°C, add carbon nanotubes and prepared microcapsules, and stir at a high speed of 800-1000 rpm for 20-30 minutes to make the carbon nanotubes evenly dispersed in the material system and the microcapsules completely and evenly embedded in the material; S7: putting the above mixed materials into a twin-screw extruder, setting the extrusion temperature to 170-200°C and the screw speed to 20-40rpm, and obtaining a balloon dilatation catheter material for prostate hyperplasia through extrusion, cooling, pulling and cutting.
2. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 1, characterized in that: In S2, the compatibilizer is specifically a maleic anhydride grafted polymer, and the cross-linking agent is specifically glutaraldehyde.
3. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 1, characterized in that: In S5, the cross-linking agent is slowly added dropwise at a speed of 0.5-1 ml / min.
4. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 1, characterized in that: The waterborne polyurethane is a waterborne polyurethane containing free amino groups.
5. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 1, characterized in that: The microcapsule is made of a wall material and an inner liquid, wherein the wall material is made of chitosan and gelatin, and the mass ratio of the chitosan to the gelatin is 3:2; the inner liquid comprises a polyurethane prepolymer containing a carbon-carbon double bond and benzophenone and glutamine aminotransferase, and the mass ratio of the polyurethane prepolymer to benzophenone is 10:
1.
6. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 5, characterized in that: The specific preparation steps of the microcapsules are as follows: S11: dissolving chitosan in a dilute acetic acid solution to prepare a chitosan solution with a concentration of 2% to 3% (w / v), dissolving gelatin in deionized water to prepare a gelatin solution with a concentration of 3% to 4% (w / v), and mixing the two solutions at 40-50° C. according to a proportion to obtain a wall material solution; S12: a polyurethane prepolymer containing a carbon-carbon double bond and benzophenone are mixed in proportion, stirred evenly, and then a proper amount of emulsifier is added to form a uniform emulsion under high-speed stirring (800-1000 rpm), and then glutamine aminotransferase is added as a catalyst contained in the microcapsules, and the added mass is 1% of the polyurethane prepolymer containing a carbon-carbon double bond; S13: slowly dropwise adding the above emulsion into the wall material solution, while stirring at a speed of 300-500 rpm, so that the emulsion is dispersed into tiny droplets in the wall material solution; S14: then adding glutaraldehyde to crosslink and solidify the wall material using glutaraldehyde, wherein the amount of glutaraldehyde added is 0.5% to 1% of the mass of the wall material solution, and the crosslinking reaction is carried out at room temperature for 2 to 3 hours, during which the mixture is continuously stirred at a rotation speed of 500 to 600 rpm; S15: After the cross-linking is completed, the microcapsules are collected by centrifugal separation, and washed with deionized water for 3-4 times to remove unreacted substances and impurities to obtain pure microcapsules.
7. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 6, characterized in that: In S12, the emulsifier is specifically a 10% to 20% (w / v) aqueous solution of behenyl alcohol polyoxyethylene ether-80.
8. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 7, characterized in that: The specific added mass of the behenyl alcohol polyoxyethylene ether-80 aqueous solution is 1% to 3% of the total mass of the polyurethane prepolymer containing carbon-carbon double bonds and benzophenone.
9. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 6, characterized in that: The specific speed of slowly dropping the emulsion into the wall material solution in S13 is 1-2 drops / s.
10. The method for preparing a balloon dilatation catheter material for prostate hyperplasia according to claim 6, characterized in that: In the S15, the microcapsules are centrifuged for 10-15 minutes at a speed of 3000-5000 rpm.
Citation Information
Patent Citations
Preparation method of tension-resistant medical conduit material and application thereof
CN108478883A
A medical EVA catheter material with a frosted surface, its preparation method and application
CN113480799B